Perspektif Mahasiswa Prodi Teologi IAKN Tarutung Tentang Persepuluhan Pada Tahun 2024 - Veronika Uliarta Sinaga; Iwan Setiawan Tarigan; Bernhardt Siburian (International Forum of Researchers and Lecturers, 2024)
This research was conducted to find out the perspective of IAKN Tarutung Theology Study Program students regarding tithing through observation and the results of interview discussions with the aim of finding out what IAKN Tarutung Theology Study Program students view regarding the practice of tithing in the church from their perspective. This research uses qualitative methods with descriptive analysis and the data source for this research is obtained by observing and conducting interviews with informants. The results of this research state that students of the Lutheran sect (GKPPD, GKPA, HKBP), this denomination have a variety of views regarding tithing, with several churches implementing it, namely: GKPPD and GKPA. and those who don't are HKBP, but all emphasize the importance of tithing as an expression of gratitude for God's commands as written in the Bible. The regulations do not require students to pay tithing, but for those who already have an income, the denomination's dogma applies tithing. Calvinist students have varying perspectives on the practice of tithing, consisting of: GKI, GBKP, GKSBS. Calvinists view that the practice of tithing is not an absolute obligation, but rather a choice in response to God's grace. They prioritize the understanding that tithing is a form of perfection in responding to God's grace, not a rule based on percentages. Meanwhile, Pentecostal students (GBI, GBIS, GPDI) state that tithing is an essential part of spiritual obedience to God. In this sect, tithing is considered a sacred act that sets aside a portion of the blessings received to be offered to God. The offering is one tenth of all the blessings. Uniquely, the GBI and GBIS denominations require mandatory tithing practices for students. Meanwhile, the GPDI denomination does not require students to tithe. Tithing is only required for members of the congregation who have a fixed income.